Need of the Study of Working Capital Management: Analyzing the importance and role of working capital in a company's operations (Journal of Advances and Scholarly Researches in Allied Education, 2013)
There are two concepts of working capital 'gross' and'net'. According to the gross concept, working capital is die total of currentassets. In turn of the net concept, working capital is die excess of currentassets over current liabilities. Unless otherwise indicated it is the latterconcept, which has been followed for the purpose of this study. This is becauseit permits a long run view of working capital of the enterprise selected forstudy. In earning a reasonable rate of return, the functional,complementary, proportional and technical role of working capital plays a greatpart. Besides, the presence of an adequate working capital also helps inmaintaining an earning a good reputation in the business world. The analysis ofworking capital should concern itself with its circulation, liquidity level andthe structural health. Preparing a fund flow statement or conducting variousratio tests can analyze the working capital position of a company. Of the twothe latter is better and of greater importance since it deals with each andevery aspects of the working capital analysis and is useful for both theinternal as well as external management. Working Capital consists of that portion of the assets ofa business, which are used, in current operations. It includes receivables,inventories or raw materials, stores, work-in-progress and finished goods,merchandise, bill receivable and cash.